Differences in resolution of mwr-containing plasmid dimers mediated by the Klebsiella pneumoniae and Escherichia coli XerC recombinases: potential implications in dissemination of antibiotic resistance genes. - Bui, D; Ramiscal, J; Trigueros, S; Newmark, J; Do, A; Sherratt, D; Tolmasky, M (2006)
Xer-mediated dimer resolution at the mwr site of the multiresistance plasmid pJHCMW1 is osmoregulated in Escherichia coli containing either the Escherichia coli Xer recombination machinery or Xer recombination elements from K. pneumoniae. In the presence of K. pneumoniae XerC (XerC(Kp)), the efficiency of recombination is lower than that in the presence of the E. coli XerC (XerC(Ec)) and the level of dimer resolution is insufficient to stabilize the plasmid, even at low osmolarity. This lower efficiency of recombination at mwr is observed in the presence of E. coli or K. pneumoniae XerD proteins. Mutagenesis experiments identified a region near the N terminus of XerC(Kp) responsible for the lower level of recombination catalyzed by XerC(Kp) at mwr. This region encompasses the second half of the predicted alpha-helix B and the beginning of the predicted alpha-helix C. The efficiencies of recombination at other sites such as dif or cer in the presence of XerC(Kp) or XerC(Ec) are comparable. Therefore, XerC(Kp) is an active recombinase whose action is impaired on the mwr recombination site. This characteristic may result in restriction of the host range of plasmids carrying this site, a phenomenon that may have important implications in the dissemination of antibiotic resistance genes.